Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1603/0022-2585(2006)43[1195:eotaca]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Temephos and Chlorpyrifos-Methyl Against <I>Culex pipiens</I> (Diptera: Culicidae) Larvae in Septic Tanks in Antalya, Turkey

Abstract: The larvicidal activity of chlorpyrifos-methyl and temephos was evaluated against Culex pipiens L. (Diptera: Culicidae) in septic tanks in Antalya, Turkey. Chlorpyrifos-methyl (Pyrifos MT 25 emulsifiable concentrate [EC] ) was evaluated at application rates of 0.04, 0.08, and 0.12 mg active ingredient (AI)/liter, and temephos (Temeguard 50 EC) was evaluated at 0.02, 0.04, and 0.06 mg (AI)/liter during a 21-d study. Generally, overall larval reduction in septic tanks from single- and multifamily dwellings treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 8 publications
1
24
0
Order By: Relevance
“…that develop in water containers or abandoned car tires in urban or peri-urban habitats in Mexico [12-15]. These findings have been substantiated and expanded upon by others that have studied container and pool dwelling mosquito species across different parts of the world [16-22]. …”
Section: Introductionmentioning
confidence: 84%
“…that develop in water containers or abandoned car tires in urban or peri-urban habitats in Mexico [12-15]. These findings have been substantiated and expanded upon by others that have studied container and pool dwelling mosquito species across different parts of the world [16-22]. …”
Section: Introductionmentioning
confidence: 84%
“…This insecticide is largely used in agriculture to control insects and mites. Some publications report the activity of the product on mosquitoes (Cetin et al, 2005), Musca domestica (Kristensen et al, 2004) and tsetse fly (De Deken et al, 2004). Two publications report the efficacy of the product on Ctenocephalides felis when administered monthly at a mean dose of 30 mg/kg (Snyder et al, 2007;Roberston-Plouch et al, 2008) The purpose of this study was to determine the duration of efficacy of a new formulation (spinosad tablets, ComfortisTM ® , Lilly Elanco) in the control of experimental infestations of adult fleas Ctenocephalides canis (Siphonaptera: Pulicidae) (Curtis, 1826) when administered once orally to Beagle dogs at the Laboratory recommended dosage (over 30 mg/kg).…”
Section: Introductionmentioning
confidence: 99%
“…Cetin et al (2005) worked on the Evaluation of the naturally derived insecticide spinosad against Culex pipiens L. (Diptera: Culicidae) larvae in septic tank water in Antalya. Additional studies have reported the larvicidal properties of spinosad in this and other mosquito species (Liu et al 2004a(Liu et al , 2004bCetin et al 2005a;Darriet et al 2005;Darriet and Corbel 2006;Romi et al 2006), or as an adulticide in a sugar bait formulation (Muller and Schlein 2006).…”
Section: Introductionmentioning
confidence: 99%